Farm management hand-book - Guerra Espinal, Guillermo (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2018)
The book is divided into two parts. The first consists of seven chapters in which the principles and methods of planning and analysis for the agricultural business are presented. The second consists of three chapters containing a practical guide for the reorganizqtion and planning of agricultural businesses. Each chapter has its own bibliography so that the reader may delve more deeply into those subjects which may be of special interest.